Climate Ethics: Individual vs. Collective Responsibility and the Problem of Corruption - Chi, Vesak (Stance: an international undergraduate philosophy journal, 2013)
Anthropogenic climate change (ACC) has been described as a tragedy of the commons (T of C) by Baylor Johnson. Johnson argues that solutions to T of C scenarios reside in collective action rather than individual action, and that our moral obligation is to advocate for collective solutions to ACC. Marion Hourdequin argues that individual action can serve to promote collective action and in doing so it can also serve as an ethical obligation. I contend that individual action holds intrinsic value in lieu of its ability to counteract our susceptibility to the kind of moral corruption espoused by Stephen Gardiner.